Effect of three natural antioxidants on the structure and physicochemical properties of sweet potato starch noodles - Weiyun Guo; Ling Fan; Yonghui Wang; Guanghui Li; Xueli Gao; Zhenhao Chen; Jihong Huang; Jihong Huang (Frontiers in Nutrition, 2022)
The study aimed to investigate the effect of three kinds of natural antioxidants (NAs), such as curcumin, tea polyphenols (TP), and lycopene, on sweet potato starch's structure and physicochemical properties of starch noodles. We found that the broken rates, iodine blue values, hardness, and chewiness of natural antioxidant starch noodles (NASN) were increased with the addition of the NAs. Additionally, the elasticity decreased with the addition of curcumin and lycopene, but it increased with the addition of TP. The cross-section structure of NASN obtained by scanning electron microscope (SEM) showed more holes appeared when adding NAs, and the additional amount had a pronounced effect on the microstructure of starch noodles (SN) regardless of the kind of NA added. The X-ray diffraction detection showed that some crystal forms were significantly damaged, and the addition of NAs affected the crystallization process of starch and produced a small proportion of new crystals in the NASNs. The protective effects of SN on NAs and their antioxidant capacities under dry and room temperature storage (DRTS) and wet and frozen storage (WFS) conditions were optimal as compared to those of flour noodles (FN). The results showed that adding NAs could improve the sensory quality and antioxidant function of starch noodles. In turn, the dense structure of starch noodles can also have a significant protective effect on antioxidants and their antioxidant activities, which is especially obvious under WFS conditions.